2008
DOI: 10.1051/0004-6361:20079218
|View full text |Cite
|
Sign up to set email alerts
|

Direction identification in radio images of cosmic-ray air showers detected with LOPES and KASCADE

Abstract: Aims. We want to understand the emission mechanism of radio emission from air showers to determine the origin of high-energy cosmic rays. Therefore, we study the geometry of the air shower radio emission measured with LOPES and search for systematic effects between the direction determined on the radio signal and the direction provided by the particle detector array KASCADE. Methods. We produce 4D radio images on time-scales of nanoseconds using digital beam-forming. Each pixel of the image is calculated for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
(6 reference statements)
2
18
0
Order By: Relevance
“…Most physics results have been obtained with this LOPES-30 setup operated until 2009, which provided statistics of about 500 high-quality events [211,212]. In particular, LOPES achieved an angular resolution of better than 0.7 • for air showers [213,201], an energy precision and accuracy of at least 20 % [194,214], and experimentally demonstrated the sensitivity of the radio signal to the longitudinal shower development [198]. However, due to the high measurement uncertainties of LOPES, the achieved X max precision was not competitive to other experiments [201,194].…”
Section: Lopesmentioning
confidence: 99%
“…Most physics results have been obtained with this LOPES-30 setup operated until 2009, which provided statistics of about 500 high-quality events [211,212]. In particular, LOPES achieved an angular resolution of better than 0.7 • for air showers [213,201], an energy precision and accuracy of at least 20 % [194,214], and experimentally demonstrated the sensitivity of the radio signal to the longitudinal shower development [198]. However, due to the high measurement uncertainties of LOPES, the achieved X max precision was not competitive to other experiments [201,194].…”
Section: Lopesmentioning
confidence: 99%
“…Using LOPES data recorded during various weather types it was shown that this amplification of the radio pulse only occurs during thunderstorm conditions [11]. In another study it was shown that the arrival direction reconstructed with radio data and particle detector data can differ by a few degrees during thunderstorms [12].…”
Section: Introductionmentioning
confidence: 97%
“…Assuming a point source would result in a spherical wavefront shape, which is used for analysis of LOPES data [11]. It is argued in [12] that the actual shape of the wavefront is not spherical, but rather conical, as the emission is not point-like but stretched along the shower axis.…”
Section: Introductionmentioning
confidence: 99%